Acupuncture for Impaired Glucose Tolerance in People With Obesity: A Protocol for a Multicenter Randomized Controlled Trial - Yan, Yan; Sun, Yuanjie; Wang, Xinlu; Zhu, Lili; Chen, Yu; Liu, Zhishun (Frontiers in Medicine, 2022)
Background: Impaired glucose tolerance (IGT) associated with overweight/obesity is a powerful risk factor for the disease of diabetes. In addition to lifestyle intervention which shows limited clinical application, acupuncture treatment has been a feasible treatment method for IGT in clinical practice. However, the effectiveness of acupuncture treatment has not been proved in evidence-based practice. Therefore, we design a multi-center randomized controlled trial to evaluate the efficacy and safety of acupuncture treatment for IGT in overweight/obese population. Methods: The trial will be conducted at hospitals in three different sites of China. A total of 196 subjects will be recruited and randomly assigned in the ratio of 1:1 to either acupuncture group or sham acupuncture (SA) group. Both groups will receive 30 sessions of treatment in the consecutive 12 weeks, provided with lifestyle intervention and 24-week follow-up. The primary outcome will be the change in the value of 2-hour blood glucose (2hPG) from baseline at the 12th week. Additionally, the expectancy of acupuncture, blinding, and safety will also be assessed. All statistical analysis will be performed in a two-sided test, with p-value less than 0.05 statically significant. Discussion: This study aims to provide quantitative clinical evidence on acupuncture effectiveness and safety in treating IGT in overweight/obese population. Clinical trial registration: Registered at ClinicalTrials.gov, registration number: NCT05347030